2012
DOI: 10.1200/jco.2012.41.9101
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Increased Primary Health Care Use in Cancer Survivors

Abstract: PHC use is significantly increased 2 to 5 years after diagnosis of cancer, especially in younger patients without a chronic disease. Given the expected increase in cancer survivors, PCPs should prepare themselves for this increasing amount of aftercare. The development of multidisciplinary care standards for cancer survivors could be helpful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 17 publications
3
58
0
1
Order By: Relevance
“…However, prior studies have reported mixed findings regarding the utilization of primary care utilization following cancer diagnosis (6,7,(12)(13)(14)(15). Our study showed that primary care and noncancer care utilization did not differ following diagnosis of cancer and might be explained by coordination of primary and specialty care services within an integrated health-care system or ongoing care for noncancer comorbidities (16).…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…However, prior studies have reported mixed findings regarding the utilization of primary care utilization following cancer diagnosis (6,7,(12)(13)(14)(15). Our study showed that primary care and noncancer care utilization did not differ following diagnosis of cancer and might be explained by coordination of primary and specialty care services within an integrated health-care system or ongoing care for noncancer comorbidities (16).…”
Section: Discussionmentioning
confidence: 44%
“…For example, patients who are undergoing cancer treatment may be less likely to receive recommended care across a number of chronic comorbid conditions (4). The impact of cancer treatment on primary care visits is unclear, with conflicting findings from prior studies (4)(5)(6)(7). Furthermore, with the rapid uptake of early detection technologies and the aging of the population, many newly diagnosed cancer patients have a higher risk of dying of other causes than their cancer.…”
Section: J Natl Cancer Inst Monogr 2014;49:275-281mentioning
confidence: 99%
“…2 Reasons for visits to the family physician and to specialists visited specialists in the past 12 months compared to the comparison group (p<0.001) [17]. Another Dutch study found an increase of 24 % in the annual number of primary care contacts among BC survivors, 2-5 years after diagnosis, in comparison with controls (p<0.001) [18]. In our study, the median number of visits to the family physician in the past year, 8-12 years after diagnosis, was 4 for cases and 3 for the comparison group (p= 0.02).…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies have also found that several years after diagnosis, cancer patients with chronic diseases have increased GP consultation rates, when compared to those without chronic disease [17,18]. These studies were also based on data from the NIVEL Primary Care Database.…”
Section: Discussionmentioning
confidence: 97%